1966
DOI: 10.1177/001872086600800205
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory Comparisons of Reaction Time Using an Electro-Pulse Tactile Stimulus

Abstract: The literature on cutaneous communication suggests that a square wave electro-pulse may be a more effective tactile stimulus for cross modality comparisons of reaction times than more traditional stimuli. It was hypothesized that the electro-pulse would give faster reaction times than either light or sound, when presented independently or in simultaneous combinations with the other stimuli. Mean reaction times of 10 male subjects, analysis of variance and mean separation test all indicated that the electro-pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Most previous research comparing unimodal stimulus presentation with bimodal presentation of correlated stimuli have shown evidence for intersensory facilitation ; better performance is produced when stimuli are presented in two modalities as opposed to only one. This result has been found with reaction time experiments (Bernstein, Clark, & Edelstein, 1969a;Swink, 1966), vigilance experiments (Buckner & McGrath, 1963), and detection studies (Brown & Hopkins, 1967;Loveless, Brebner, & Hamilton, 1970). Handel and Buffardi (1969) have also shown that simultaneous auditory and visual stimulus presentation produces a faster rate of pattern identification than does individual modality presentation.…”
Section: University Of Portlandsupporting
confidence: 52%
“…Most previous research comparing unimodal stimulus presentation with bimodal presentation of correlated stimuli have shown evidence for intersensory facilitation ; better performance is produced when stimuli are presented in two modalities as opposed to only one. This result has been found with reaction time experiments (Bernstein, Clark, & Edelstein, 1969a;Swink, 1966), vigilance experiments (Buckner & McGrath, 1963), and detection studies (Brown & Hopkins, 1967;Loveless, Brebner, & Hamilton, 1970). Handel and Buffardi (1969) have also shown that simultaneous auditory and visual stimulus presentation produces a faster rate of pattern identification than does individual modality presentation.…”
Section: University Of Portlandsupporting
confidence: 52%
“…A number of experiments have demonstrated that reaction time (RT) to a signal can be modified by the presentation of a secondary stimulus m conjunction with the primary signal. Some investigators have found a longer RT to double stimulation, even though the secondary stimulus required no response from the S (Koster & Bekker, 1967, Nickerson, 1967 Presentation of stimuli to 2 sensory modalities has, however, produced contrasting results, since mtersensory experiments commonly show a facilitation of RT by the accessory stimulus (Bernstein, 1970, Swink, 1966, Symons, 1963 It is clear that either facilitation or inhibition of RT may result from double stimulation, depending upon a number of experimental variables…”
mentioning
confidence: 99%